Rancangan Alat Evaporator Vertical Long Tube untuk Pembuatan Kalsium Klorida dari Batu Kapur - Anjani, Dewi; Fitri, Ayu Chandra Kartika; Anggraini, Sinar Perbawani Abrina (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Calcium chloride, which has the chemical formula CaCl2, is a type of intermediate salt formed from the elements calcium (Ca) and chlorine (Cl2). This component has a variety of applications, including being empowered as an ice melting agent, as dust control on the streets during the summer, as an industrial process material, as an oil and gas separation material, as a concrete making material and others. This research is aimed at determining the dimensions of the Vertical Long Tube Evaporator type for the calcium chloride production process. The working principle of the Vertical Long Tube Evaporator involves a number of long tubes positioned vertically in the evaporation vessel. The solution to be evaporated is fed into the evaporator, this can be a solution containing solvents or other liquids that need to be removed through evaporation. Heating is carried out on the tube walls with an operating temperature of 110ºC using assistance from an external heat source in the form of steam with a temperature of 128ºC coming from the Boiler. Calcium chloride solution entering the Evaporator has a capacity of 3,694.6172 kg / hour. The final results of the calculation obtained the dimensions of the Vertical Long Tube type Evaporator with a vessel diameter of 1.3716 m, the total height of the vessel is 3.3595 m. There is a torisferical type cap at the top measuring 0.3429 m and the bottom cap of the conical type has a size of 1.1878 m so that the volume of the vessel is 2.2296 m3 / hour, the number of tubes is 58 pieces with a diameter of 0.0254 m and the length is 1.2192 m. There are 4 supporting columns of the I-beam type measuring 2.4418 m in harmony with the foundation of the I-beam foundation measuring 2.4418 m in harmony with the foundation of the I-beam. There are 4 support columns of the I-beam type measuring 2.4418 m aligned with a foundation made of cement and gravel 0.508 m high and a bottom area of 0.762 m. Abstrak Kalsium klorida, yang memiliki rumus kimia CaCl2, termasuk suatu jenis garam intermediate yang terbentuk dari unsur kalsium (Ca) dan klorin (Cl2). Komponen ini memiliki beragam aplikasi, di antaranya diberdayakan sebagai zat pencair es, sebagai pengendalian debu di jalan-jalan ketika musim panas, sebagai bahan proses industri, sebagai bahan pemisahan minyak dan gas, sebagai bahan pembuatan beton dan lain-lain. Penelitian ini ditujukan untuk menentukan dimensi ukuran alat Evaporator berjenis Vertical Long Tube untuk proses produksi kalsium klorida. Prinsip kerja Evaporator Vertical Long Tube melibatkan sejumlah tabung panjang yang diposisikan secara vertikal didalam bejana evaporasi. Larutan yang akan diuapkan, dimasukkan ke dalalm Evaporator, ini bisa berupa larutan yang mengandung pelarut atau cairan lain yang perlu dihilangkan melalui penguapan. Pemanasan dilakukan pada dinding tabung (tube) dengan suhu operasi 110ºC menggunakan bantuan dari sumber panas eksternal berupa steam dengan suhu 128ºC yang berasal dari Boiler. Larutan kalsium klorida yang masuk ke Evaporator berkapasitas 3.694,6172 kg/jam. Hasil akhir dari perhitungan diperoleh dimensi Evaporator jenis Vertical Long Tube dengan diameter bejananya adalah 1,3716 m, tinggi total bejananya adalah 3,3595 m yang terdapat tutup jenis torisferikal pada bagian atas berukuran 0,3429 m dan tutup bagian bawah berjenis konikal memiliki ukuran 1,1878 m sehingga diperoleh volume bejana adalah 2,2296 m3/jam, jumlah tube sebanyak 58 buah yang berdiameter 0,0254 m serta panjangnya adalah 1,2192 m. Terdapat 4 buah kolom penyangga yang jenisnya I-beam berukuran 2,4418 m selaras dengan pondasi berbahan semen dan gravel setinggi 0,508 m serta luas bagian bawah 0,762 m.